To Change or Not to Change: Reflections on the Role Games Play in Maintaining Psychic Equilibrium. (April 2015) - Heath, Lis; Oates, Steff
This article considers whether a legacy in transactional analysis of overinvesting in change and the analysis or avoidance of games can lead to a foreclosure of important emergent processes in psychotherapy. The authors do not advocate a preferred way of working with games, recognizing that offering an antithesis often leads to establishing further doctrine. Instead, they describe two ways of understanding clients' need to maintain equilibrium and relate this to game theory. They explore the dialectic between interpersonal analysis of games and the value of giving more space to clients' intrapsychic processes.